MENDARAS MANUNGGALING KAWULA GUSTI SYEKH SITI JENAR - Sidqi, Ahmad (Jurnal Dinamika Penelitian: Media Komunikasi Penelitian Sosial Keagamaan, 2017)
that make Jenarâs controversial is a God-theme things, that make hakikatis most important things than syariâat. Manunggaling kawula Gusti as ahogher thing of Jenar also gift a controversial status to Jenar. It can happened,because the approachment of Jenar too less of manunggaling kawula Gusti,that is language approachment. Need an approacment objectively of Jenar,Human being is a human that showing if empthy actually Full (Jenarâswith his thought, actually not been himself as God, but on his thought, Jenarwant to say that God is One.Keyword: Syekh Siti Jenar, Tasawuf, Manunggaling Kawula Gusti,